Inner Worlds: Individuals and Interiority in Chinese Religious Life - Benn, James A.; Brose, Benjamin (Asian Studies E-Books Online, Collection 2026., 2025)
How do the inner convictions of individuals clash and sometimes cohere with the ideologies of their times? This volume investigates the interior lives of Chinese religious practitioners from the tenth century to the present to explore their dreams, visions, and personal struggles. The reader will encounter an eminent Buddhist master's Confucian dreams, a Qing court lama's visions of China, and a modern Chan master's memories of his own awakening. The contributors draw on a vast array of sources-poetry, dream records, confessions, instructional talks, and previously unpublished archival documents-to offer a new perspective on the interplay between personal belief and political ideology, between the otherworldly and the mundane. Contributors are: James A. Benn, Ester Bianchi, Raoul Birnbaum, Benjamin Brose, Daniela Campo, Wen-shing Chou, Vincent Goossaert, Ji Zhe, Paul R. Katz, Beverley McGuire, Gray Tuttle, and Wang Jia.